« Mâle ou normal ? ». Incarnation et masculinité(s) du couple Hollande-Sarkozy dans la campagne présidentielle de 2012 - Marlène Coulomb-Gully (Genre, Sexualité et Société)
After the French presidential election of 2007 with Ségolène Royal as one of the two main candidates, the last election appears as « back to normal » with two men as finalists. Even so, the question of gender was at the hart of the campaign : Nicolas Sarkozy and François Hollande embody their masculinity quite differently, with the media playing their part in the construction of these strategic identities. The first part of this research is called « Embodying France » : it deals with the most concrete aspects of embodiment (the shape, the hair, the voice of the candidates) ; the second part is called « The Chief’s Plumage » and deals with more symbolic aspects of embodiment; the third part focuses on the women (mainly the spouses of the two candidates) and their role in the construction of the candidates strategic identities.